Narrative Report: Theory of Change - Nuapada Onion Value Chain Learning Lab - Jain, Harsha; Puskur, Ranjitha; Dwivedi, Anushka; Shivhare, Richa; Muckhopadhyay, Prama; Chadha, Deepali; Goel, Kritika; Gartaula, Hom N. (CGIAR Initiative on Gender Equality, 2024)
This Theory of Change Narrative is for one such Learning Lab (LL) set up by the International Rice Research Institute (IRRI) in collaboration with one of the institutions within the Indian Council of Agricultural Research (ICAR), namely ICAR - Indian Veterinary Research Institute (ICAR-IVRI). The Learning Lab will have various partners to support activities including research and operations. The LL is embedded in ICAR-IVRI’s Scheduled Caste Sub-Plan (SCSP) and Scheduled Tribe Sub-Plan (STSP) project, aimed to increase the income of the target population through diverse income-generating schemes, skill enhancement initiatives, and infrastructure and to reduce poverty.